Nursing of integrated traditional Chinese and western medicine for a patient with neurogenic bladder (1 例神经源性膀胱患者的中西医结合护理体会) - ZHENG Yingqian (郑莹芊); XU Jing (许静); ZOU Qiuyu (邹秋玉) (Journal of International Translational Medicine Limited, 2023)
This paper summarized the nursing of integrated traditional Chinese and western medicine for a patient with neurogenic bladder. Based on assessment of patient's recovery needs, the rehabilitation plan generated by a multidisciplinary team was carried out, including exercise training, umbilical moxibustion, acupuncture, intermittent catheterization and home-based extended care. Integrative nursing intervention is potentially effective to improve the reconstruction of the urinary function and reduce the residual urine volumes. (本文总结1例神经源性膀胱患者的中西医结合护理经验。评估患者康复需求, 多学科团队合作制定康复方案, 采用康复锻炼、脐灸、针灸、间歇性导尿、家庭延续护理等的中西医联合干预方法, 加快患者下尿路功能的重建和部分重建, 提高控尿能力、减少残余尿量, 患者成功拔除尿管, 可自控小便。)